RITUAL NGALAB BERKAH DALAM MENCARI KEKAYAAN DI GUNUNG KEMUKUS - Triyanto Triyanto (Jurnal Community, 2015)
Every society in the world has a culture, and every culture has is a system of beliefs held by the community. Likewise community actors in Kemukus ritual that has its own beliefs about how to find fortune by doing free sex. The conviction was strung in a ritual which known as ngalab berkah. This ritual begins from a myth that spoken by the RA Ontrowulan towards moksha as a royal family that promise to grant all requests of people who participated in Kemukus nyonggo wirang. The existence of this ritual is able to increase the local economy, as evidenced that is the emergence of jobs for the community. But it on the other hand it also cause negative impacts such as raises prostitution. It becomes an interesting phenomenon, because if this ritual is closed, then many people will be unemployed. Meanwhile if left unchecked, would be bad for society. To describe this ritual conception it was conducted qualitative research. The result is the people have a conception which is the influence of Hindu-Buddhist and animist dynamism, especially about the king who is believed to be manifestation of God. Based on this conception ritual actors believe the myth, so that conception nyonggo wirang is a form of defense and the participation of actors ritual with the pathos of the character who is the royal family, so it is not impossible if the request will be met.